Boosting Oxygen Evolution Reaction on Metallocene‐based Transition Metal Sulfides Integrated with N‐doped Carbon Nanostructures. Issue 22 (14th October 2021) - Thangasamy, Pitchai; Nam, Sanghee; Oh, Saewoong; Randriamahazaka, Hyacinthe; Oh, Il‐Kwon
Abstract: In this study, utilizing metallocene and organosulfur chelating agent, an innovative synthetic route was developed towards electrochemically activated transition metal sulfides entrapped in pyridinic nitrogen‐incorporated carbon nanostructures for superior oxygen evolution reaction (OER). Most importantly, the preferential electrochemical activation process, which consisted of both anodic and cathodic pre‐treatment steps, strikingly enhanced OER and long‐lasting cyclic stability. The substantial increase in OER electrocatalytic activity of Ni9 S8 /Ni3 S2 −NC and Co9 S8 −NC during the activation process was mainly attributed to the increase of faradaic active site density on the catalytic layer resulting from the reconstruction of catalytic interfaces. It was also found that Fe‐based metallocene [ferrocene (Fc)]‐incorporation in the Co9 S8 −NC and Ni9 S8 /Ni3 S2 −NC nanostructures significantly boosted the OER activity. Thus, the combined effects of Fc‐incorporation and the electrochemical activation process reduced the overpotential to about 115 and 95 mV on the Ni9 S8 /Ni3 S2 −NC and Co9 S8 −NC nanostructures to derive a current density of 10 mA cm −2, respectively. Notably, Fc−Ni9 S8 /Ni3 S2 −NC electrocatalysts required very small overpotentials of around 222, 244, and 280 mV to acquire the current densities of 10, 20, and 50 mA cm −2, respectively. This work opens up a new avenue for superior OER electrocatalysts by the utilization of metallocene and the preferential electrochemical activation process. Abstract : Electrochemical activation : Low‐valent transition metal sulfides entrapped in pyridinic nitrogen‐incorporated carbon nanostructures are fabricated by utilizing metallocene and organosulfur chelating agent, and the electrochemical activation process is exploited to significantly ameliorate their electrocatalytic oxygen evolution activity.